NOKEN LOCAL WISDOM AS REPRESENTATION OF GOD'S LOVE - Titus Pikei; Adison Adrianus Sihombing (Al-Qalam, 2023)
This study aims to describe, explore and analyze the local wisdom of noken as a symbol of Papuan culture which has a strong religious-spiritual meaning for the lives of the Papuan people. This study was compiled using a qualitative research design by relying on primary data obtained through interviews and observations of the daily life of women who make noken and use noken in Papuan society. The informants involved were religious leaders, community leaders and noken women. The findings of the study are that noken is Papuan life, as a vessel and source of life that contains religious-spiritual values. Noken is interpreted as a representation of God's love for Papua which fosters faith and hopes in the Creator. In addition, noken is seen as a second 'womb'. Children born are put in a noken as a container for growth and development until they are crawling. Furthermore, a special noken was made for children with the aim of practicing honesty. If a child takes food from someone else's noken, it means stealing. Stealing means sin according to custom and religion. Noken is not just known but has existed and is known from time to time, passed down and taught how important it is to live in Papuan noken human life. Thus noken is a representation of God's inclusion and maintenance of Papuan life. The ancestors of the Papuan people were explorers living on the island of Papua using the strategy of the regional language of the tribes in the land of Papua to teach noken, namely Ugatame. This means that God is the Creator of the heavens and the earth and humans who are similar to Him. The aim is for the Papuan people to have more faith in God Allah.